(untitled) (Journal of the Sylhet Agricultural University, 2025)
The experiment was conducted at the farmers’ fields of Bahadurpur and Noagaon village at Sadarupazilla and Dakshin Sunamganj, respectively under the Dekharhaor (wetland) of Sunamganj district, Bangladesh during November, 2015 to May 2016 to observe the nutrients concentration and uptake by the local fine rice varieties under different rates of fertilizers application. The experiment comprised four varieties viz. Tapiboro (V1), Begun bichi (V2), Rata boro (V3), Atobshail (V4), and three fertilizers package treatments- F1= Farmers’ practice, FP (NPK @ 41.4-4.2-10.5 kg ha-1), F2= Recommended Fertilizer Dose, RFD (NPKSZn@69-22.4-31.7-6.7-0.65 kg ha-1) and F3= Soil test based fertilizers, STB (NPKSZn@61-17.5-33.5-3.1-0.7 kgha-1). The experiment was laid out in two factors Completely Randomized Block Design (RCBD) with three farmers’ replications. Data were collected on yield, nutrients concentration and uptake of rice. Tapiboro produced the highest grain yield of 3.10 tha-1and straw yield of 5.49 tha-1. The grain and straw yield varied significantly due to application of different fertilizer doses. Application of STB fertilizer were produced the highest grain yield of 2.95 tha-1 and straw yield of 4.85 tha-1. The highest amount of NPKSZn concentration was found in Tapiboro and application of STB fertilizers. Tapiboro uptakes the highest amount of NPKSZn. The NPSZn apparent balance was found positive and negative K balance was found in all treatments. Tapiboro with STB based fertilizers application was the best option in the haor area for the farmers’. J. Sylhet Agril. Univ. 11(2): 43-52, 2024